2013
DOI: 10.1021/jp308990x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Thermal Reaction of Short-Chain Alcohols on Ge(100)

Abstract: The adsorption and thermal decomposition of alcohols (CH 3 OH, C 2 H 5 OH, and C 4 H 9 OH) on Ge(100) were investigated with temperature-programmed desorption and Xray photoelectron spectra. At 105 K, CH 3 OH adsorbs both molecularly and dissociatively on Ge(100). Chemisorbed CH 3 OH molecules dissociate to form surface CH 3 O and hydrogen in a temperature range 150−300 K. Surface CH 3 O can dehydrogenate to yield CH 2 O as two desorption features, which depend on coverage. At small coverage, surface CH 3 O un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…In Figure 2b, we observed a single O 1s peak at 530.9 eV, which is assigned to the OÀ H dissociated structure, according to previous research on a Ge(100) surface, where the O 1s peak related to OÀ H dissociated species with a neutral oxygen atom emerges at 530.6-531.5 eV. [12,28,29] Hence, we suggest that 1-propanol reacts with the Ge(100) surface via OÀ H dissociation. As shown in Figure 2e, we resolved the C 1s signal as two distinct peaks at 284.4 and 285.5 eV.…”
Section: Resultssupporting
confidence: 76%
“…In Figure 2b, we observed a single O 1s peak at 530.9 eV, which is assigned to the OÀ H dissociated structure, according to previous research on a Ge(100) surface, where the O 1s peak related to OÀ H dissociated species with a neutral oxygen atom emerges at 530.6-531.5 eV. [12,28,29] Hence, we suggest that 1-propanol reacts with the Ge(100) surface via OÀ H dissociation. As shown in Figure 2e, we resolved the C 1s signal as two distinct peaks at 284.4 and 285.5 eV.…”
Section: Resultssupporting
confidence: 76%
“…A previous investigation has reported that the binding energy of the C 1s peak corresponding to molecularly absorbed Ge–OHCH 3 was observed at 286.3 eV because the carbon atom in the methyl group is influenced by the positively charged oxygen atom next to it. 18 Therefore, we assigned the peak at 286.3 eV to C α because of the effect of the adjacent positively charged oxygen atom bonded to this carbon atom. When tetrahydrofuran and diethyl ether molecules are adsorbed on Si(100) via the formation of O dative bonds, the difference in the binding energies between C α and C β was in the range of 1.0–1.5 eV.…”
Section: Resultsmentioning
confidence: 99%
“… 2 , 13 16 The analogous reactions used in organic chemistry are relatively well known on a Si(100) surface, 17 whereas those performed on Ge(100) are limited as a result of the differences in the chemical reactivity and electronic structures between the two surfaces. 15 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Attempts to introduce the pentyloxycarbonyl group directly on an unprotected 5 0deoxy-fluorocytidine led to the development of new reagents, different from the usual 615 pentylchloroformate, able to selectively functionalize the N-4. With this purpose in mind, starting from N-hydroxysuccinimide 143 , a new pentylcarbonate 130 was recently prepared in 98% yield that selectively functionalized the unprotected 5 0 -deoxy-fluorocytidine at N-4, affording capecitabine 63 in 44% yield (Scheme 73).…”
Section: Synthesis Of Antitumor Fluorinated Pyrimidine Nucleosides 41mentioning
confidence: 99%